(untitled) (Journal of Telenursing (JOTING), 2024)
This study aims to determine the application of audiovisual education methods to improve knowledge of anemia in pregnant women. The method in this study used a pre-experiment design with a one-group pretest-posttest design with a sample size of 34 pregnant women. The results obtained using the t-dependent test showed a p-value of 0.000 <0.005, so H0 was rejected and Ha was accepted, the average (mean) between knowledge of anemia pre-test with a mean result of 53.48 and post-test with a mean result of 94.024. The conclusion is that there is a difference in the average (mean) between before and after using audiovisual education methods on knowledge of anemia in pregnant women. Keywords: Anemia, Audiovisual, Education, Pregnant Women, Knowledge